ANTI-ATHEIST NATION - Klug, Petra, author. ([S.l.])
1 online resource.
Keywords: Atheists are a growing but marginalized group in the American religious patchwork and they have been the target of ridicule and discrimination throughout the nation's history. This book is the first comprehensive study of anti-atheism in the United States. It traces anti-atheism through five centuries of American history from colonization to the era of Donald Trump and contemporary conspiracy ideologies, such as the atheist New World Order. Describing anti-atheist prejudices and explaining the social and psychological mechanisms behind anti-atheist attitudes, it will appeal to scholars of sociology, religious studies and history with interests in religion in the United States.